Influêngia de adições de prata na dureza da liga Cu-13%Al - De Arruda, Gilberto José; Adorno, Antonio Tallarico [UNESP]; Beatrice, Carlos Roberto Sobreira [UNESP]; Cilense, Mário [UNESP] (My University, 1996)
The influence of silver additions on the Cu-13 wt. pct. Al alloy hardness was studied for additions in the range 0 to 16 wt. pct. Ag. The results indicated a pronounced hardness increase with the silver content and an influence of the quenching temperature. Data obtained from scanning electron microscopy indicated that the formation of silver-rich precipitates, wich change with the quenching temperature, seems to produce the changes on alloys hardness.
Influence of silver additions on the Cu-13 wt. pct. Al alloy hardness
Keywords: Ag additions; Cu-based alloys; Microhardness; Scanning electron microscopy